التكوين الاكاديمي المتخصص و انعكاساتهعلى جودة الاداء المهني - بشرى كميتي; د/ طارق مريقي (جامعة عمار ثليجي الاغواط, 2024)
ملخص الدراسة : تمثل دراستنا هذه في تقديم تحليل شامل للعلاقة بين التكوين الأكاديمي والأداء المهني للمراسل الصحفي، مع تقديم توصيات لتحسين برامج التكوين الأكاديمي وضمان توافقها مع احتياجات سوق العمل المتغيرة في مجال الصحافة والإعلام. من خلال هذه الدراسة ، نسعى إلى تعزيز جودة الأداء المهني للصحفيين في الجزائر والمساهمة في تطوير إعلام مهني ومسؤول يخدم المجتمع بفعالية. إشكالية الدراسة :ما الدور الذي يلعبهالتكوين الأكاديمي المتخصص في تحسين جودة الأداء المهني للمراسل الصحفي بالأغواط؟ اهم النتائج المتحصل عليها : • أهمية تطوير المناهج لتشمل الجوانب التقنية وطرق التحكم في وسائل الاتصال والإعلام الحديثة. • الجامعات لها دور كبير في تأهيل العنصر البشري الكفؤ لتلبية احتياجات سوق العمل المتغيرة. • على الجامعات ألا تركز فقط على الجانب النظري بل تشمل الجانب التطبيقي والتقني بشكل أكبر. الكلمات المفتاحية : الاذاعة ، العمل الصحفي ، التكوين الأكاديمي Abstract : Our study aims to provide a comprehensive analysis of the relationship between academic training and the professional performance of journalists, along with recommendations to enhance academic training programs and ensure their alignment with the evolving needs of the media industry. Through this study, we seek to improve the quality of journalistic performance in Algeria and contribute to the development of a professional and responsible media that effectively serves society. Research Problem: What is the role of specialized academic training in the quality of professional performance for journalists? Key Findings: • The importance of developing curricula to include technical aspects and methods of controlling modern communication and media channels. • Universities play a significant role in preparing competent human resources to meet the changing needs of the job market. • Universities should not only focus on theoretical aspects but also incorporate practical and technical aspects to a greater extent. Keywords: Broadcasting, Journalism, Academic Training
دراسة ميدانية على عينة من صحفي اذاعة الجزائر بالاغواط